Investigation Of Impact Strain Signal Characteristics For Material Behaviour Prediction From Charpy Test - Muhammad Said, Nurlaela (2019)
This thesis investigates impact strain signal analysis during Charpy impact test. Impact strain signals were used to examine strain signal patterns under various parameters. It is includes the correlation between energy absorbed with power spectrum density (PSD) and area under strain-time graph at different material, impact speed and thickness of material. Thickness effect on impact duration is presents as well. Besides that, stress-strain curve is relates with the impact strain signal. Recently, the number of accident on highway has been increased due to loss of structure integrity to withstand high impact load. Therefore, materials that have ability to provide adequate protection to passengers from harmful and improve occupants' survivability during crash event are needed. Tough material with high energy absorption capability is required to reduce damage on structure when high impact energy is applied. Impact test is often performed to determine toughness of material by determine the amount of energy absorbs. However, most of energy absorbed is not accurate and only calculated as an estimation value. This scenario brings an idea to correlate the energy absorbed with strain energy by installing strain gauge to striker hammer that connected to data acquisition system (SOMAT eDAQ). Besides that, mechanical testing of tensile test is carried out to obtain the material behaviour and to identify the material properties that being used in calculation of impact duration. Results indicate a great correlation is observed between energy absorbed with strain energy. Strain energy is directly proportional to the energy absorbed. In term of material's type,Aluminium 6061-T6 shows a good energy absorber compared to the Magnesium AM60 because aluminium is more ductile than magnesium. Impact duration of experiment, theory and previous study shows a same pattern where it was increased if material's thickness is increased but decreased when applied speed is increased. Relation of strain signal from Charpy test and stress-strain curve from tensile test shows a great finding where the material deforms and fracture points is identified through the strain pattern and stress-strain curve. Aluminium 6061-T6 has the highest of energy absorbed, maximum strain and strain energy under PSD graph compared to Magnesium AM60. This concludes that characteristics of strain signal from Charpy test needs to be classified as an alternative method to predict properties of a material.